The Kindergarten Readiness of Children Playgroup Based on Model of Learning Center - Maria Hidayanti (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims to determine the kindergarten  of children Playgroup based on model of learning centers and how the stimulation that is provided by teachers when learning activities. The research was conducted in the plygroup Bunda Balita class of 15 children. This study uses qualitative research methods are manifold phenomenology. Analysis of data using the model of Miles and Huberman step as for step (1) Reduction data (2) The presentation of data, (3) Drawing conclusion/verification. Data collected by observation, interview and use NST assay to measure the school readiness of children. The resulst of this study showed the playgroup. The stimulation provided by the teacher from the morning until noon through habituation activities, axemplary and stimulation when learning with questioning methods, storytelling, free play and play at the center, singing and practice. This study is find things that can better support the  methods and provides the tools to play a more varied again, the need to enhance the creativity of teachers in creating other types of play activities